Mubādalah in Practice: Exploring the Dual Role of Generation Z Students as Couples - Zaid, Muhammad; Noor, Safdhinar Muhammad An; Utami, Defanti Putri; Mustofa, Yoki Bisry (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2024)
Applying the principle of reciprocity within a household is crucial for maintaining family resilience. However, implementing this principle often poses challenges for young families, particularly when one or both partners are still university students. This study focuses on how married students at the State Islamic University of Maulana Malik Ibrahim Malang apply the concept of mubādalah (reciprocity). Using a sociological approach, the research gathered data through in-depth interviews with six students, comprising three male and three female participants. The findings reveal that several students acknowledged that their marriages were founded on mutual values and collaboration, which are representations of mubādalah. The study also highlights that these students successfully navigate dual roles as spouses and students by integrating the principles of mubādalah. They regard this concept as a critical foundation for fostering happiness and family resilience in their lives. The application of mubādalah enables both partners to share responsibilities equitably, transforming marriage into a collaborative and mutually beneficial partnership. These findings affirm that marriage during study, despite academic commitments, does not hinder personal growth. Instead, it demonstrates the practical application of reciprocal and equitable role-sharing practices, which benefit both individuals in the partnership.